Le plurilinguisme du perroquet - Manuel Mühlbacher (Flaubert: Revue Critique et Génétique)
The figure of the parrot holds an ambiguous position towards the question of translation. It is able to imitate all languages, but it will never understand any of them – its only skill is to mimic sounds, i.e. mere signifiers. On the contrary, the translator seems to be the antithesis of the parrot when he moves from one language to another. He endeavours to convey a similar meaning, but by different signs. The article aims at discussing the role of the translator and his or her eventually equivocal relation to the parrot by means of analysing the German translation of Trois Contes by André Stoll and Cora van Kleffens. Whereas a semantic divergence can result in a different tendency on the level of interpretation, as in the case of an underlying allusion in the French text that is made explicit in the translation, the transfer of the French syntax into German can provoke serious difficulties. How can the translator reproduce syntactic structures that do not exist in German, but that frequently occur in French? What measures can he or she take when the text acts the role of the parrot and apes itself? André Stoll and Cora van Kleffens have developed a strategy able to meet these problems.